INVESTIGASI EKSPERIMENTAL KARAKTERISTIK KEKUATAN TARIK PADUAN RESIN FLEKSIBEL-STANDAR UNTUK MATERIAL 3D PRINTING - Dyaksa, Gilang Argya; Nugraha, Felix Krisna Aji; Hermawan, Oktavianus Nekson; Putra, Mahendra Pratama; Astyanto, Achilleus Hermawan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Over the years, technologies of 3D printing have enhanced the opportunity to ease the production of complex geometries. In particular, it further implies that the flexibility of materials is of a great importance. Therefore, the works covering studies of applicability on novel materials in rapid prototyping contribute to the development of additive manufacturing. The present work experimentally investigates a mechanical property, namely tensile strength, of 3D printing materials on the basis of the concentration of flexible-standard resins. Tensile strengths were obtained by a series of tensile tests. Here, the result reveals that the tensile strength monotonously decreases as the increase of the concentration of flexible resin’s concentration. Moreover, an ANOVA analysis strongly implies a consistent relationship between the tensile strength and the material’s mixture.